FACTORS ASSOCIATED WITH THE SEXUAL FUNCTION OF PREGNANT WOMEN: A CROSS-SECTIONAL STUDY - Vieira Pereira, Emanuelly (2023)
Objective: To identify factors associated with the domains of sexual function and psychophysical correlates of pregnant women at habitual risk. Materials and methods: A cross-sectional, quantitative study carried with 354 pregnant women at usual risk in the interior of Ceará, Brazil. A form and the Sexuality in Pregnancy Questionnaire were used for data collection. Results: There was a reduction in all domains of sexual function and of the psychophysical correlates of lubrication and sexual satisfaction, when compared to the pre-pregnancy period. Only the psychophysical correlate pain/sexual discomfort increased during pregnancy and was significant by gestational trimester. Variables related to sexual behavior and symbolic aspects influenced the changes observed. Schooling positively influenced sexual desire and orgasm intensity. No variables associated with reduced sexual pain/discomfort were identified. Conclusions: Factors related to sexual behavior, symbolic aspects (perception) and education were associated with changes in the domains of sexual function and psychophysical correlates of pregnant women at habitual risk.